Transforming growth factor-β-mediated CD44/STAT3 signaling contributes to the development of atrial fibrosis and fibrillation - Chang, Shang-Hung; Yeh, Yung-Hsin; Lee, Jia-Lin; Hsu, Yu-Juei; Kuo, Chi-Tai; Chen, Wei-Jan (Basic research in cardiology, 2017)
Atrial fibrillation (AF) is associated with atrial fibrosis. Inhibition of atrial fibrosis might be a plausible approach for AF prevention and therapy. This study is designed to evaluate the potential role of CD44, a membrane receptor known to regulate fibrosis, and its related signaling in the pathogenesis of atrial fibrosis and AF. Treatment of cultured rat atrial fibroblasts with transforming growth factor-β (TGF-β, a key mediator of atrial fibrosis) led to a higher expression of hyaluronan (HA), CD44, STAT3, and collagen (a principal marker of fibrosis) than that of ventricular fibroblasts. In vivo, TGF-β transgenic mice and AF patients exhibited a greater expression of HA, CD44, STAT3, and collagen in their atria than wild-type mice and sinus rhythm subjects, respectively. Treating TGF-β transgenic mice with an anti-CD44 blocking antibody resulted in a lower expression of STAT3 and collagen in their atria than those with control IgG antibody. Programmed stimulation triggered less AF episodes in TGF-β transgenic mice treated with anti-CD44 blocking antibody than in those with control IgG. Blocking CD44 signaling with anti-CD44 antibody and mutated CD44 plasmids attenuated TGF-β-induced STAT3 activation and collagen expression in cultured atrial fibroblasts. Deletion and mutational analysis of the collagen promoter along with chromatin immunoprecipitation demonstrated that STAT3 served as a vital transcription factor in collagen expression. TGF-β-mediated HA/CD44/STAT3 pathway plays a crucial role in the development of atrial fibrosis and AF. Blocking CD44-dependent signaling may be a feasible way for AF management.